2007
DOI: 10.4102/sajim.v9i1.18
|View full text |Cite
|
Sign up to set email alerts
|

Nine drivers of knowledge transfer between universities and industry R&D partners in South Africa

Abstract: This article presents part of the findings of the Research Marketing and Technology Commercialization Survey conducted in South Africa during 2005 and 2006. Part IV (Q4) of this survey was designed to examine nine drivers of knowledge transfer between South African universities in their research and development (R&D) collaborations with industry firms. Respondents from a judgemental sample ranked the knowledge transfer for R&D collaboration between university departments and industry as: (a) the need t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 125 publications
1
9
0
Order By: Relevance
“…Thus, a very generous financial reward via IP and innovation policy will go a long way in encouraging academics within the universities and personnel in informal and formal sectors to disclose IP for possible protection to newly established TTOs. It is worth mentioning that IP and innovation policy that encourage the strategic collaboration between local and/or international business and this offices, as reported in this study, is supported by other studies [70,71] which demonstrated that such partnership is key to the successful transfer of technology from universities to industry/market. Nevertheless, for sustainable newly established TTO-business partnerships, effective engagement mechanisms beneficial to both parties must be enacted.…”
Section: Intellectual Property and Innovation Policysupporting
confidence: 78%
“…Thus, a very generous financial reward via IP and innovation policy will go a long way in encouraging academics within the universities and personnel in informal and formal sectors to disclose IP for possible protection to newly established TTOs. It is worth mentioning that IP and innovation policy that encourage the strategic collaboration between local and/or international business and this offices, as reported in this study, is supported by other studies [70,71] which demonstrated that such partnership is key to the successful transfer of technology from universities to industry/market. Nevertheless, for sustainable newly established TTO-business partnerships, effective engagement mechanisms beneficial to both parties must be enacted.…”
Section: Intellectual Property and Innovation Policysupporting
confidence: 78%
“…In order for the diaspora to engage in their countries of origin, governments must put mechanisms and regulatory bodies in place to better channel the efforts and contributions of this capital. This includes improving a socio-political environment that fosters the hatching of engineering, the development of intelligence and the promotion of excellence, offering incentives, as was shown in the examples of the Asian countries such as South Korea, India, and China (Hatcheu, 2004;Van Zyl, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…The knowledge that being transmitted in this research based from Fleck's table (1997) is cultural knowledge in the context of recipe knowledge that is knowledge on prescriptions for action (Van Zyl 2007). Transferring knowledge is necessary preserving cultural knowledge on skill and technique of preparation traditional foods (Nor et al 2012).…”
Section: Knowledge Transfermentioning
confidence: 99%